Biotic and abiotic drivers of dipterocarp seedling survival following mast fruiting in Malaysian Borneo. (March 2015) - Oshima, Chiaki; Tokumoto, Yuji; Nakagawa, Michiko
Abstract: South-East Asian tropical rain forests experience sporadic, but profuse, seed production after general flowering, leading to the synchronous emergence of various seedlings and subsequent seedling dynamics, which play a crucial role in determining species distribution and coexistence. We examined the relative importance of both biotic (initial height, conspecific seedling density) and abiotic (canopy openness, per cent sand, soil water content) drivers using survival data for 1842 seedlings of 12 dipterocarp species for 1.5 y following mast fruiting in an old-growth Bornean tropical rain forest. More than 30% of all dipterocarp seedlings survived 1.5 y after mast fruiting. When all species were analysed together, we found that initial seedling height, canopy openness and conspecific seedling density affected dipterocarp seedling survival. Negative density dependence indicated that predators were not satiated, but dipterocarp seedlings rather suffered from host-specific natural enemies or intraspecific competition. Species-level analyses of seven dipterocarp species showed large variation in response to biotic and abiotic factors. These results suggest that interspecific differences in the relative importance of biotic and abiotic effects on seedling survival might contribute to species coexistence.